Impact of Blended Learning Techniques on Skill Acquisition in Chinese Classical Dance Among University Students - Xie, Xinfei; Husain, Adzira Binti (Journal of Teaching and Learning, 2026)
This study aims to evaluate the effectiveness of blended learning strategies in skill acquisition for Chinese classical dance among university students. A cross-sectional survey was conducted with 120 university students to assess various aspects of blended learning. Independent t-tests and linear regression analyses were used to examine how different blended learning variables affected skill improvement in Chinese classical dance. Additionally, thematic analysis was used to explore the challenges and advantages students reported when applying blended learning principles to dance education. The results indicate that blended learning significantly enhances skill development in Chinese classical dance compared to traditional teaching methods. Specifically, the duration of blended learning, instructors' experience with the method, and session frequency all contributed to improved dance skills. The study concludes that blended learning is an effective educational model for enhancing skill acquisition in Chinese classical dance. It combines the benefits of face-to-face and online learning, offering a flexible and collaborative approach to teaching.